Profil Pasien Dewasa dengan Gangguan Pendengaran di Poliklinik THT-KL RSUP Prof. Dr. R. D. Kandou - Yves Villeneuve; Moudi M. Mona; Steward K. Mengko (e-CliniC, 2026)
Abstract: Hearing loss can affect individuals of all ages and has significant impacts on communication, social functioning, and overall quality of life. Its prevalence continues to rise with advancing age and exposure to various risks factors. This study aimed to obtain the profile of patients with hearing loss at the ENT clinic of Prof. Dr. R. D. Kandou General Hospital during the 2023 to 2024 period. This was a descriptive retrospective study using electronic medical record data that met the inclusion criteria. The analyzed variables included age, sex, residence, occupation, diagnosis, type of hearing loss, severity of hearing loss, and management. Data were presented as frequency and percentage distributions. The results obtained a total of 134 patients that met the inclusion criteria. The highest percentages of distribution were adult age group (50.75%), male patients (52.24%), from outside of Manado City (67.16%), occupation as housewife (29.10%), diagnosed as hearing loss (38.81%), followed by chronic suppurative otitis media (21.64%) and impacted cerumen (11.19%). Mixed hearing loss was the predominant type (48.51%), and severe level of hearing loss (34.32%). The most frequent management provided was hearing aids (59.70%). In conclusion, the majority of hearing loss cases were mixed hearing loss with severe level. The majority of patients were male in the adult age group and recieved hearing aids. Keywords: types of hearing loss; mixed hearing loss   Abstrak: Gangguan pendengaran dapat dialami semua kelompok usia dan berdampak pada komunikasi, fungsi sosial, serta kualitas hidup. Prevalensi kondisi ini terus meningkat dengan bertambahnya usia dan paparan faktor risiko. Penelitian ini bertujuan untuk mendeskripsikan profil pasien gangguan pendengaran pada orang dewasa di Poliklinik THT-KL RSUP Prof. Dr. R. D. Kandou Manado periode 2023-2024. Jenis penelitian ialah deskriptif retrospektif menggunakan data rekam medis elektronik pasien yang memenuhi kriteria inklusi. Variabel yang dianalisis ialah usia, jenis kelamin, tempat tinggal, pekerjaan, diagnosis, jenis gangguan pendengaran, derajat keparahan, dan penatalaksanaan. Data dipresentasikan dalam bentuk distribusi frekuensi dan presentase. Hasil penelitian mendapatkan sebanyak 134 pasien yang memenuhi kriteria penelitian. Persentase penyebaran tertinggi didapatkan pada kelompok usia dewasa (50,75%), jenis kelamin laki-laki (52,24%), dan berasal dari luar Kota Manado (67,16%), pekerjaan mengurus rumah tangga (29,10%), diagnosis hearing loss (38,81%), diikuti OMSK (21,64%) dan impacted cerumen (11,19%). Jenis gangguan dominan ialah mixed hearing loss (48,51%) dan keparahan derajat berat (34,32%). Penatalaksanaan terbanyak berupa pemberian alat bantu dengar (59,70%). Simpulan penelitian ini ialah mayoritas gangguan pendengaran yaitu mixed hearing loss dengan derajat keparahan berat. Mayoritas pasien berjenis kelamin laki-laki dalam kelompok usia dewasa dan mendapatkan alat bantu dengar. Kata kunci: jenis gangguan pendengaran; mixed hearing loss